2001
DOI: 10.4049/jimmunol.166.3.1690
|View full text |Cite
|
Sign up to set email alerts
|

High-Avidity CTL Exploit Two Complementary Mechanisms to Provide Better Protection Against Viral Infection Than Low-Avidity CTL

Abstract: Previously, we observed that high-avidity CTL are much more effective in vivo than low-avidity CTL in elimination of infected cells, but the mechanisms behind their superior activity remained unclear. In this study, we identify two complementary mechanisms: 1) high-avidity CTL lyse infected cells earlier in the course of a viral infection by recognizing lower Ag densities than those distinguished by low-avidity CTL and 2) they initiate lysis of target cells more rapidly at any given Ag density. Alternative mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
170
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 39 publications
(36 reference statements)
11
170
1
Order By: Relevance
“…22,23 This so-called functional avidity maturation may occur though cross-linking of receptors, 24 activation-induced cholesterol enrichment of membranes, 24 or changes in signal transduction. 22,25 Studies have revealed that higher avidity T cells generate stronger antigen-specific antiviral 26,27 or antitumor 9,18,19 effects. Derby et al 27 observed that following viral infection, high-avidity CTL mediate earlier antigen recognition because of higher sensitivity to antigen than low-avidity T cells and initiate antigen-specific lysis more rapidly than low-avidity T cells.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 This so-called functional avidity maturation may occur though cross-linking of receptors, 24 activation-induced cholesterol enrichment of membranes, 24 or changes in signal transduction. 22,25 Studies have revealed that higher avidity T cells generate stronger antigen-specific antiviral 26,27 or antitumor 9,18,19 effects. Derby et al 27 observed that following viral infection, high-avidity CTL mediate earlier antigen recognition because of higher sensitivity to antigen than low-avidity T cells and initiate antigen-specific lysis more rapidly than low-avidity T cells.…”
Section: Discussionmentioning
confidence: 99%
“…DCs were grown from bone marrow by cultivating in CM with 1”g/ml GMCSF for 5 days. The P18-I10-specific T-cell line MHb (Derby et al, 2001a) was maintained in CM containing 10% T-Stim Culture Supplement (BD Biosciences, San Jose, CA). Every 10 days T cells were restimulated with addition 0.5 nM P18-I10 peptide and irradiated splenocytes from BALB/c mice.…”
Section: Mice Cell Isolation and Cell Linesmentioning
confidence: 99%
“…It also includes a term for inter-clonal competition among the effector cells for infected cells expressing a single epitope. It appears that high-and low-avidity CTL lyse their targets at similar rates (Derby et al, 2001), so we set k c to be the same for all T cell clones in our model. In LCMV responses, the value of k c was found to be 12 day À1 (Barchet et al, 2000).…”
Section: Clearance Of Infected Cellsmentioning
confidence: 99%